Monitoring the coastal zone using earth observation: application of linear spectral unmixing to coastal dune systems in Wales. Issue 4 (23rd April 2018) - Ettritch, Georgina; Bunting, Peter; Jones, Gwawr; Hardy, Andy
Abstract: Coastal sand dune systems across temperate Europe are presently characterized by a high level of ecological stabilization and a subsequent loss of biological diversity. The use of continuous monitoring within these systems is vital to the preservation of species richness, particularly with regard to the persistence of early stage pioneer species dependent on a strong sediment supply. Linear spectral unmixing was applied to archived Landsat data (1975–2014) and historical aerial photography (1941–1962) for monitoring bare sand (BS) cover dynamics as a proxy for ecological dune stabilization. Using this approach, a time series of change was calculated for Kenfig Burrows, a 6‐km 2 stabilized dune system in South Wales, during 1941–2014. The time series indicated that a rapid level of stabilization had occurred within the study area over a period of 75 years. Accuracy assessment of the data indicated the suitability of medium‐resolution imagery with an RMSE of <10% across all images and a difference of <3% between observed and predicted BS area. Temporal resolution was found to be a significant factor in the representation of BS cover with fluctuations occurring on a sub‐decadal scale, outside of the margin of error introduced through the use of medium‐resolution Landsat imagery. This study demonstrates a tractable approach for mapping and monitoring ecologically sensitive regions at a sub‐Landsat pixel level. Abstract : Coastal sand dune systems across temperate Europe are presently characterized by a high level of ecological stabilization and a subsequent loss of biological diversity. We applied linear spectral unmixing to archived Landsat data (1975–2014) and historical aerial photography (1941–1962) for monitoring bare sand (BS) cover dynamics as a proxy for ecological dune stabilization. Using this approach, we calculated a time series of change during 1941–2014 for Kenfig Burrows, a 6‐km 2 stabilized dune system in South Wales. The time series indicated that a rapid level of stabilization had occurred within the study area over a period of 75 years, and temporal resolution was found to be a significant factor in the representation of BS cover. This study demonstrates a tractable approach for mapping and monitoring ecologically sensitive regions at a sub‐Landsat pixel level.